Dysphagia Evaluation in a Multidisciplinary VA Cognitive Care Clinic. (20th December 2022) - Mackowicz, Meredith; Yee, Joanne; Clark, Lindsay R.; Wanninger, Ellen; Lewis, Brian Lee Young; Kuntz, Aaron; Robison, Raele; Kind, Amy J.; Rogus‐Pulia, Nicole M.
Abstract: The VA Cognitive Care Clinic (CCC) provides comprehensive evaluation and longitudinal treatment for older Veterans with neurocognitive disorders and their caregivers through multidisciplinary care including geriatrics, palliative medicine, neuropsychology, and social work. Speech‐language pathology (SLP) was recently incorporated into the CCC team in response to calls for more proactive approaches to diagnosis and management of dysphagia (swallowing dysfunction) in persons with dementia. While dysphagia is estimated to be highly prevalent in this population, prior work has been limited by inadequate dementia characterization. The purpose of this novel quality improvement project was to provide descriptive information regarding the occurrence of dysphagia in persons with dementia seen in CCC. CCC patients underwent comprehensive neuropsychological and geriatrics assessments that led to a multidisciplinary determination of dementia diagnosis and subtype. Validated dysphagia‐specific clinical evaluation tools included the Eating Assessment Tool (EAT‐10; dysphagia‐specific patient‐reported outcome measure), the 3‐ounce water swallow test to assess swallowing safety (aspiration risk), and the Test of Masticating and Swallowing Solids (TOMASS) to assess swallowing efficiency. A REDCap database was constructed to track CCC evaluation results and patient‐specific variables derived from the electronic health record. Descriptive statistics were calculated for dementia diagnosis, subtype, and dysphagia measures. 124 patients were seen in CCC between 2017 and 2021. Eighty‐eight patients (73%) received a dementia diagnosis with the majority meeting criteria for Alzheimer's disease (53%) or mixed etiology (24%). Sixty‐eight (55%) of these patients were evaluated by an SLP during their initial intake appointment. Twenty of 59 patients (39%) scored 3 or higher on the EAT‐10, indicating concern for dysphagia. Twenty‐six of 64 patients (41%) failed the 3‐ounce water swallow test. Thirty‐one of 62 patients (50%) demonstrated inefficient mastication based on length of total masticatory time on the TOMASS. Findings from this initial cohort indicate that approximately one‐half of patients with dementia assessed by a SLP demonstrated clinical signs of swallowing safety or efficiency impairment. Patient report of dysphagia‐related symptoms occurred at a significantly lower rate, supporting the need for SLP services in multidisciplinary memory and geriatrics clinics to facilitate early identification of dysphagia and avoid serious dysphagia‐related consequences, including pneumonia and malnutrition.